Design in the process of teaching mathematics and its teaching methodology - Nafasov Ganisher Abdurashidovich; Usmonov Navroz Muzaffarovich; Nazirov Qobiljon Qosim o‘g‘li; Dushabayev Olimjon (Genius Journals, 2023)
This article studied the comparative analysis of the drafting of the educational process of higher educational institutions in foreign countries and the Republic and its implementation in practice, using as a template the methodology for designing the educational process of Mathematical Sciences in higher educational institutions of the Republic and using them in educational practice.
Keywords: Educational technology; pedagogical technology; methodology